Studies on Long- Term Storage of Sperm of a Marine Ornamental Fish, Istiblennius edentulus (Perciformes: Blennidae) - P.S., Sivaprasad; C.E., Paul; P., Natarajan; V., Jayaprakas (Fishery Technology, 2025)
Detailed study was conducted on the effect of cryopreservation on spermatozoa of a marine ornamental fish of the family Blennidae. The long-term preservation of spermatozoa of Istiblennius edentulus was conducted with 5 different extenders in combination with 5%, 7.5% and 10% concentrations of DMSO, Methanol and Glycerol as cryoprotectants. The best post thaw motility was observed with Alsever's solution as extender and 5% Glycerol as cryoprotectant (88.12%motility and 89.19% viability).